The Extraordinary Solution for Indonesia Economic Crisis: Shariah Capital Market - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The historical development of the Islamic finance industry which includes banking, insurance and capital markets is fundamentally a very long historical process. The Islamic Shariah principles applied in the banking industry and Cairo is a country founded the first Islamic bank around 1971 under the name